Registration of 'HoCP 09‐804' Sugarcane. Issue 2 (14th February 2019) - Todd, James; Dufrene, Edwis; Pan, Yong-Bao; Tew, Thomas; White, William; Hale, Anna; Duet, Michael; Verdun, David; Grisham, Michael; Petrie, Eric; Gravois, Kenneth; Waguespack, Herman; et al.
Abstract : 'HoCP 09‐804' (Reg. No. CV‐184, PI 688682) sugarcane (interspecific hybrid of Saccharum spp.) was selected and evaluated by the USDA‐ARS, working cooperatively with the Louisiana State University AgCenter and the American Sugarcane League, Inc. HoCP 09‐804 was selected from a cross between 'HoCP 02‐625' and 'HoCP 01‐523' made at the USDA‐ARS, Sugarcane Field Station, Canal Point, FL, in 2004 and was released to growers in Louisiana in 2016 because of high cane and sucrose yields. Yields from three crops (plant, first‐, and second‐ratoon) at 12 outfield locations compared well with 'L 01‐299', the most widely grown cultivar in Louisiana. The plant‐cane sugar yield (Mg ha −1 ) of HoCP 09‐804 was significantly greater than L 01‐299. The sucrose content (g kg −1 ) was second only to 'HoCP 00‐950', the standard for high sucrose. HoCP 09‐804 was among the earliest maturing cultivars, ranking second only to HoCP 00‐950, and cold tolerant, similar to 'HoCP 04‐838'. HoCP 09‐804 is mildly susceptible to smut, leaf scald, and ratoon stunt. HoCP 09‐804 is susceptible to brown rust and mosaic caused by Sorghum mosaic virus . It is moderately susceptible to sugarcane borer. This cultivar's high yield potential, ratooning ability, and cold tolerance make it a useful addition to existing commercial sugarcane cultivars in Louisiana.